O efeito de regras sobre o estabelecimento, generalização e manutenção de relatos verbais acurados em tarefas acadêmicas - Pereira, Letícia Rinolfi (Universidade Federal de São Carlos, 2026)
Studies in the area of say–do correspondence have predominantly investigated the role of consequences (i.e., correspondence training) in the establishment of accurate reporting in children, whereas the role of antecedent manipulations remains less explored. The present study evaluated the effects of two types of rules on the establishment, generalization, and maintenance of accurate reporting of errors in academic tasks. Six typically developing children aged 6 to 8 years participated in a computerized task organized in a do–say sequence. The do component consisted of reading words and answering mathematics questions presented by the computer. The say component consisted of reporting correct and incorrect responses after hearing feedback with the correct answer, by clicking on a green square (correct) or a red square (incorrect). During baseline, the accuracy of error reporting was assessed in the absence of differential consequences and rules for both reading and mathematics tasks. In the subsequent condition, a rule was presented by the experimenter at the beginning of each session only for the task with the lowest level of accuracy during baseline. Three participants were exposed to a rule describing positive social consequences for accurate reports, and three were exposed to a rule describing negative social consequences for inaccurate reports. All participants showed low to intermediate levels of accuracy during baseline, which were lower in the reading task for four participants and in the mathematics task for two. The introduction of rules, regardless of rule type, produced high levels of accuracy for all participants within a few sessions (three to five). This pattern was maintained after rule withdrawal, and generalization was observed to the task not directly exposed to the rule. The results suggest that rules are effective in establishing, generalizing, and maintaining accurate reporting in children.
The effect of rules on the establishment, generalization, and maintenance of accurate verbal reports in academic tasks
Keywords: Correspondência fazer-dizer; Relato verbal; Regras; Generalização; Manutenção; Say–do correspondence; Verbal report; Rules; Generalization; Maintenance; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO; 4. Educação de Qualidade; 3. Saúde e Bem-Estar